The Effect Of Using The Power Of Two On Students’ Reading Comprehension On Descriptive Text At 1th Grade Of SMA N 1 Pangkalan - Nabila Nada Islami; Eliza Eliza; Hilma Pami Putri; Genta Sakti (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was done due to several problems on the students’ ability and impact to the score in reading comprehension.The first problem because the students do their task alone, the second problem the students had low motivation to read the text, the last problem the students felt bored with learning model used. The researher expected wether the power of two strategy is able to give significant effect on students’ reading comprehension. This research was an experimental research. The researcher chose quasi experimental design by using the experimental class and control class. The population of this research was 1th grade of SMA N 1 Pangkalan. The sample was X MIPA 1 which was as treated experimental class and X MIPA 2 was treated as control class. To determine the sample, the researcher used cluster sampling because the class have similar characteristic in score of reading test and have similar problems in reading comprehension.The researcher used the reading test as instrument.To analyzed the data, the researcher used Liliefors test for normality test. Then to test the hypothesis, the researcher used t-test and Based on the analysis of the data, the result was also indicated by the mean of experimental class pre-test score which was 60.36. It was higher than the control class pre-test score which was 49.29. The result was also indicated by the mean of experimental class post-test score which was 85.86. It was higher than the control class post-test score which was 61.86. It meant there was significant effect of using the power of two strategy on students reading comprehension. It was concluded that Ha was accepted and H0 was rejected. The students who were taught by using the power of two strategy better than the students who were not taught by using the power of two strategy. To sum up, the power of two strategy has a significant effect on students reading comprehension on descriptive text at 1th grade of SMA N 1 Pangkalan.